Production and casting process for cylinder block with stable metallographic structure

By adjusting the composition of aluminum alloy and heat treatment technology, combined with the use of modified coatings, the problem of unstable metallographic structure of the cylinder seat at high temperatures is solved, its strength and wear resistance are improved, and its service life is extended.

CN119220833APending Publication Date: 2024-12-31SHAOGUAN JINBAO FOUNDRY CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411181606.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-27
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The metallographic structure of the existing cylinder seats is unstable at high temperatures, resulting in insufficient strength and wear resistance, affecting the performance and life of mechanical equipment.

Method used

By adjusting the composition of the aluminum alloy, including aluminum, manganese, zinc, chromium, antimony, silicon, titanium, molybdenum, nickel, vanadium and magnesium, smelting and centrifugal casting under nitrogen conditions, combined with heat treatment and surface coating treatment, Form a stable metallographic structure. Modified titanium carbide, graphene oxide and epoxy resin are used in the coating to improve surface hardness and wear resistance.

Benefits of technology

It achieves the improvement of the stability and hardness of metallographic structure, extends the service life of the cylinder seat, and improves its wear resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005012334160000121
    Figure BDA0005012334160000121
Patent Text Reader

Abstract

The invention relates to a production and casting process for a cylinder block with a stable metallographic structure, and belongs to the technical field of metal material preparation. Comprising the following steps: S11, smelting; s12, forming is conducted; s13, heat treatment; s14, carrying out surface treatment; according to the invention, by adjusting metal components in the material of the cylinder block and through temperature smelting at different stages, mold casting molding and heat treatment, elements in the alloy are fully dissolved and uniformly distributed, so that segregation and precipitated phases in the alloy are reduced, the stability of the alloy is improved, and the cylinder block with a stable metallographic structure is obtained; and the surface is coated, so that the wear resistance of the cylinder block is improved, the stability of the cylinder block is further improved, and the service life of the cylinder block is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal material preparation and relates to a production casting process for a cylinder seat with stable metallographic structure. Background Art

[0002] The primary function of the cylinder seat is to fix and position the cylinder. In an engine or similar mechanical equipment, the cylinder seat firmly fixes the cylinder in place through bolts or other fastening devices to ensure the stability and accuracy of the cylinder during operation. This stability and accuracy is crucial to the overall performance and life of the mechanical equipment, and requires high precision in its processing. At the same time, the strength of the alloy cylinder seat is also a problem that needs to be considered in processing and manufacturing.

[0003] Alloy materials with stable metallographic structure play an important role in improving material properties, optimizing processing and performance, extending service life and expanding application areas. With the continuous advancement of science and technology and the rapid development of industry, the application prospects of these alloy materials will be broader.

[0004] Therefore, it is necessary to prepare a cylinder seat with a stable metallographic structure so as to have excellent wear resistance and strength. Summary of the invention

[0005] The purpose of the present invention is to provide a casting process for producing a cylinder seat with a stable metallographic structure. The prepared cylinder seat has a stable metallographic structure, high hardness and good wear resistance.

[0006] The purpose of the present invention can be achieved by the following technical solutions:

[0007] A casting process for producing a cylinder seat with a stable metallographic structure, comprising the following steps:

[0008] S11. Smelting:

[0009] Under nitrogen conditions, 80-90 parts of aluminum, 9-13 parts of manganese, 3-5 parts of zinc, 5-8 parts of chromium, 1-3 parts of antimony, 10-15 parts of silicon, 5-8 parts of titanium, 2-5 parts of molybdenum, 3-5 parts of nickel, 3-5 parts of vanadium, and 3-5 parts of magnesium are stirred evenly by weight, added into a 570-600°C boiler and kept for 0.5-1h, heated to 670-700°C and kept for 2-3h, then the temperature is raised to 800-850°C for refining for 3-5h, and degassed after refining, and degassed at a temperature of 650-700°C for 4-5h to prepare a refined liquid;

[0010] S12, molding:

[0011] The refined liquid is centrifugally casted at a speed of 1100 to 1300 r / min at 700 to 750° C., poured into a mold, molded, cooled by cooling water, and after solidification, the temperature is maintained at 300 to 320° C. for 20 to 23 hours, and finally air-cooled to room temperature to obtain a formed cylinder seat;

[0012] S13, heat treatment:

[0013] The formed cylinder seat is heated to 350-380°C at a speed of 4-6°C / s, kept warm for 0.5-1.5h, then cooled to room temperature by air cooling at a speed of 5-7°C / s, then heated to 400-450°C at a speed of 7-10°C / s, kept warm for 1-2h, and then slowly cooled to room temperature by cooling water at a cooling speed of 2-3°C / s;

[0014] S14, Surface treatment:

[0015] The heat-treated cylinder seat is trimmed, washed with water, and dried, and then coated on the surface with a coating thickness of 10 to 20 μm to obtain the cylinder seat with a stable metallographic structure.

[0016] As a preferred technical solution of the present invention, in step S12, the temperature of the mold is 450-500°C.

[0017] As a preferred technical solution of the present invention, in step S12, the flow rate of the cooling water is 10-20m 3 / h.

[0018] As a preferred technical solution of the present invention, in step S14, the coating preparation process is as follows:

[0019] S41. At room temperature, titanium carbide, graphene oxide and ethanol in a mass ratio of (25-30): (5-10): (50-70) are mixed by ultrasound, the pH of the suspension is adjusted to 6-7 with acetic acid, the mixture is stirred for 2-4 hours, the temperature is increased to 105-115° C., the mixture is dried and crushed to prepare pretreated titanium carbide;

[0020] S42. At 50-60°C, add glycine and pretreated titanium carbide in a mass ratio of 1:1 to deionized water, perform ultrasonic treatment for 0.5-1h to obtain a uniformly dispersed mixed solution, continue to heat to 100-110°C, evaporate the water under stirring, collect the obtained solid and dry it in a vacuum drying oven; under nitrogen conditions, calcine the dried solid at 920-1000°C for 2-3h, cool naturally to room temperature, and grind it in a ball mill at a speed of 400r / min for 3-5h to obtain nitrogen-doped titanium carbide, that is, modified titanium carbide;

[0021] S43. At room temperature, 25 to 30 parts by mass of modified titanium carbide, 10 to 20 parts of tungsten carbide, 1 to 3 parts of polyethylene glycol 200 and 70 to 80 parts of anhydrous ethanol are subjected to ultrasonic treatment at a power of 500 to 600 W for 2 to 3 hours, the temperature is raised to 85 to 100° C., and after complete drying, the mixture is ground with 2 to 5 parts of molybdenum disulfide in a ball mill at a speed of 400 r / min for 3 to 5 hours, and passed through a 200-mesh sieve to prepare a modified filler;

[0022] S44, adding 2 to 5 parts of an organosilicon modifier and 1 to 2 parts of a silane coupling agent to 90 to 100 parts of an epoxy resin, and preparing a modified epoxy resin after ultrasonic dispersion at 80 to 85° C.;

[0023] S45, stirring 50-60 parts of modified epoxy resin, 3-5 parts of dispersant, and 0.5-1 part of defoamer at a speed of 600-700 r / min for 1-1.5 hours, then adding 15-20 parts of modified filler, 5-8 parts of talcum powder and 3-5 parts of curing agent, increasing the speed to 850-1000 r / min and continuing stirring for 1-2 hours, mixing completely and filtering through a 200 mesh sieve to obtain a coating;

[0024] S46. Sandblast the surface of the cylinder seat substrate. Use 20-30 mesh white corundum for sandblasting. The pressure of compressed air during sandblasting is 0.4-0.6 MPa, the sandblasting distance is 100-150 mm, and the sandblasting angle is 70-90°.

[0025] S47, spraying the coating on the surface of the cylinder seat substrate treated in step S46 by ultrasonic spraying, and leaving the sample to stand until it is completely cured and dried to obtain a cylinder seat with a coating on the surface.

[0026] As a preferred technical solution of the present invention, in step S44, the organosilicon modifier is one of hydroxy silicone oil and polydimethylsiloxane.

[0027] As a preferred technical solution of the present invention, in step S44, the silane coupling agent is one of KH550, KH560 or KH570.

[0028] As a preferred technical solution of the present invention, in step S45, the curing agent is one of diaminodiphenylmethane and isophoronediamine.

[0029] As a preferred technical solution of the present invention, in step S45, the dispersant is one of sodium carboxymethyl cellulose, sodium carboxyethyl cellulose and polyethylene glycol 200.

[0030] As a preferred technical solution of the present invention, in step S45, the defoaming agent is one of BYK-065, BYK-024 and Tego-901.

[0031] As a preferred technical solution of the present invention, in step S47, the parameters of the ultrasonic spraying are: ultrasonic power of 50-60 W, ultrasonic frequency of 120-180 kHz, and spraying distance of 30-60 mm.

[0032] In the present invention, by adjusting the metal components in the cylinder seat, adding stable metals Al and Ti, the creep resistance and high temperature resistance of the alloy are improved. Various metal elements can improve the metallographic stability of the alloy through different mechanisms. Nickel in the alloy can stabilize the phase structure and prevent phase change at high temperature, thereby improving the metallographic stability of the alloy; at the same time, the solid solution strengthening effect of chromium can enhance the matrix strength of the alloy and also help improve the metallographic stability of the alloy; by controlling the smelting temperature of the alloy, the atomic movement rate in the alloy can be slowed down, phase change and element diffusion can be avoided, and these processes can improve the stability of the alloy. At the same time, through heat treatment, the alloy is heated to a certain temperature and kept warm for a period of time, so that the elements in the alloy are fully dissolved and evenly distributed, and then quickly cooled to a uniformly distributed state, so that the segregation and precipitation phase in the alloy can be eliminated, and the stability of the metallographic structure of the alloy can be improved.

[0033] In the present invention, titanium carbide is fully and evenly mixed with graphene oxide by a solution impregnation method, and graphene oxide can form a uniformly distributed layered structure on the surface of titanium carbide. Relying on this structure, titanium carbide can be effectively and evenly dispersed in the coating, thereby helping to reduce internal defects and stress concentration points of the filler, thereby further improving the hardness and wear resistance of titanium carbide; and a lubricating layer can be formed during the drying and compounding process, thereby reducing the direct contact between titanium carbide and other materials, thereby reducing wear; and nitrogen-doped titanium carbide is obtained by high-temperature calcination with glycine, and nitrogen doping can change the crystal structure and chemical bonding mode of titanium carbide with graphene oxide loaded on the surface, forming finer grains and more uniform phase distribution, thereby improving its hardness; at the same time, due to nitrogen doping, the surface active sites of titanium carbide are increased, which can improve the interface bonding force between titanium carbide loaded with graphene oxide and other materials, and reduce the wear caused by interface desorption or peeling.

[0034] Molybdenum disulfide is added when modifying titanium carbide and tungsten carbide to prepare modified fillers. Molybdenum disulfide has a layered structure and low shear strength, so it can effectively reduce the friction coefficient, thereby reducing the wear of the coating during the friction process; at the same time, when molybdenum disulfide is ball-milled with the filler, it can also utilize its own lubricity, which can not only help reduce friction during the ball milling process, but also form a lubricating film on the surface of the modified filler, thereby helping the modified filler to improve its compatibility with the polymer matrix when preparing the coating, thereby further protecting the coating and substrate and improving the overall wear resistance and stability.

[0035] When preparing the coating, the epoxy resin is modified by silicone. Silicone contains abundant silicon-oxygen bonds, which can maintain stability and improve the chemical resistance of the epoxy resin. At the same time, the main chain structure of the silicone molecule is introduced to improve the flexibility, wear resistance and abrasion resistance of the epoxy resin. The epoxy resin is connected to the functional groups on the silicone molecular chain through a silane coupling agent, thereby improving the adhesion and bonding strength of the modified epoxy resin.

[0036] Beneficial effects of the present invention:

[0037] In the present invention, the metal components in the cylinder seat material are adjusted, and the elements in the alloy are fully dissolved and evenly distributed through temperature smelting, mold casting and heat treatment at different stages, thereby reducing segregation and precipitation phases in the alloy and improving the stability of the alloy, thereby obtaining a cylinder seat with a stable metallographic structure; and coating treatment is performed on the surface to improve the wear resistance of the cylinder seat, further improve the stability of the cylinder seat, and extend the service life of the cylinder seat. DETAILED DESCRIPTION

[0038] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.

[0039] The epoxy resin in the present invention was purchased from Jinan Shanhai Chemical Technology Co., Ltd., with the product number HYSZ01.

[0040] Example 1

[0041] S11. Smelting:

[0042] Under nitrogen conditions, 80 parts of aluminum, 9 parts of manganese, 3 parts of zinc, 5 parts of chromium, 1 part of antimony, 10 parts of silicon, 5 parts of titanium, 2 parts of molybdenum, 3 parts of nickel, 3 parts of vanadium, and 3 parts of magnesium were mixed evenly by weight, added into a 570°C boiler and kept for 0.5h, heated to 670°C and kept for 2h, and then the temperature was raised to 800°C for refining for 3h, and degassed after refining, and degassed at a temperature of 650°C for 4h to prepare a refined liquid;

[0043] S12, molding:

[0044] At 700℃, the refined liquid is centrifugally cast at a speed of 1100r / min, and the refined liquid is poured into the mold. The temperature of the mold is 450℃, and the mold casting is performed with a flow rate of 10m 3 / h of cooling water is used for cooling, and after solidification, the temperature is maintained at 300°C for 20 hours, and finally air-cooled to room temperature to obtain a formed cylinder seat;

[0045] S13, heat treatment:

[0046] The molded cylinder seat is heated to 350°C at a speed of 4°C / s, kept at this temperature for 0.5h, then cooled to room temperature by air cooling at a speed of 5°C / s, then heated to 400°C at a speed of 7°C / s, kept at this temperature for 1h, and then slowly cooled to room temperature by cooling water at a cooling speed of 2°C / s;

[0047] S14, Surface treatment:

[0048] After the heat-treated cylinder seat is trimmed, washed with water, and dried, a coating treatment is performed on the surface, and the coating thickness is 10 μm to obtain the cylinder seat with a stable metallographic structure.

[0049] The coating preparation process is as follows:

[0050] S41, at room temperature, titanium carbide, graphene oxide and ethanol in a mass ratio of 25:5:50 were mixed by ultrasound, the pH of the suspension was adjusted to 6 with acetic acid, stirred for 2 hours, the temperature was increased to 105° C., and the mixture was dried and crushed to prepare pretreated titanium carbide;

[0051] S42. At 50°C, add glycine and pretreated titanium carbide in a mass ratio of 1:1 to deionized water, ultrasonically treat for 0.5h to obtain a uniformly dispersed mixed solution, continue to heat to 100°C, evaporate the water under stirring, collect the obtained solid and dry it in a vacuum drying oven; under nitrogen conditions, calcine the dried solid at 920°C for 2h, cool naturally to room temperature, and grind it in a ball mill at a speed of 400r / min for 3h to obtain nitrogen-doped titanium carbide, that is, modified titanium carbide;

[0052] S43, at room temperature, 25 parts by mass of modified titanium carbide, 10 parts of tungsten carbide, 1 part of polyethylene glycol 200 and 70 parts of anhydrous ethanol were subjected to ultrasonic treatment at a power of 500 W for 2 hours, the temperature was raised to 85° C., after being completely dried, the mixture was ground with 2 parts of molybdenum disulfide in a ball mill at a speed of 400 r / min for 3 hours, and passed through a 200-mesh sieve to prepare a modified filler;

[0053] S44, adding 2 parts of hydroxy silicone oil and 1 part of KH550 to 90 parts of epoxy resin, and preparing a modified epoxy resin after ultrasonic dispersion at 80° C.;

[0054] S45, 50 parts of modified epoxy resin, 3 parts of sodium carboxymethyl cellulose, and 0.5 parts of BYK-065 were stirred at a speed of 600 r / min for 1 hour, and then 15 parts of modified filler, 5 parts of talc and 3 parts of diaminodiphenylmethane were added, the speed was increased to 850 r / min and stirring was continued for 1 hour. After being completely mixed, the mixture was filtered through a 200 mesh sieve to obtain a coating;

[0055] S46. Sandblast the surface of the cylinder seat substrate. Use 20-mesh white corundum for sandblasting. The pressure of compressed air during sandblasting is 0.4 MPa, the sandblasting distance is 100 mm, and the sandblasting angle is 70°.

[0056] S47. Spray the coating on the surface of the cylinder seat substrate treated in step S46 by ultrasonic spraying. After coating, let the sample stand until it is completely cured and dried to obtain a cylinder seat with a coating on the surface. The ultrasonic power is 50 W, the ultrasonic frequency is 120 kHz, and the spraying distance is 30 mm.

[0057] Example 2

[0058] S11. Smelting:

[0059] Under nitrogen conditions, 85 parts of aluminum, 10 parts of manganese, 4 parts of zinc, 6 parts of chromium, 2 parts of antimony, 12 parts of silicon, 6 parts of titanium, 3 parts of molybdenum, 4 parts of nickel, 4 parts of vanadium, and 4 parts of magnesium were mixed evenly by weight, added into a 580°C boiler and kept for 0.8h, heated to 680°C and kept for 2.5h, and then the temperature was raised to 830°C for refining for 4h, and degassed after refining, and degassed at a temperature of 670°C for 4.5h to prepare a refined liquid;

[0060] S12, molding:

[0061] At 720℃, the refined liquid is centrifugally cast at a speed of 1200r / min, and the refined liquid is poured into the mold. The temperature of the mold is 470℃, and the mold casting is performed with a flow rate of 15m 3 / h of cooling water, and after solidification, the temperature is maintained at 310°C for 21 hours, and finally air-cooled to room temperature to obtain a formed cylinder seat;

[0062] S13, heat treatment:

[0063] The molded cylinder seat is heated to 360°C at a speed of 5°C / s, kept at this temperature for 1 hour, then cooled to room temperature by air cooling at a speed of 6°C / s, then heated to 430°C at a speed of 8°C / s, kept at this temperature for 1.5 hours, and then slowly cooled to room temperature by cooling water at a cooling speed of 2.5°C / s;

[0064] S14, Surface treatment:

[0065] After the heat-treated cylinder seat is trimmed, washed with water, and dried, a coating treatment is performed on the surface, and the coating thickness is 15 μm to obtain the cylinder seat with a stable metallographic structure.

[0066] The coating preparation process is as follows:

[0067] S41, at room temperature, titanium carbide, graphene oxide and ethanol in a mass ratio of 26:7:60 were mixed by ultrasound, the pH of the suspension was adjusted to 6 with acetic acid, the mixture was stirred for 3 hours, the temperature was increased to 110° C., the mixture was dried and crushed to prepare pretreated titanium carbide;

[0068] S42. At 55°C, add glycine and pretreated titanium carbide in a mass ratio of 1:1 to deionized water, ultrasonically treat for 0.7h to obtain a uniformly dispersed mixed solution, continue to heat to 105°C, evaporate the water under stirring, collect the obtained solid and dry it in a vacuum drying oven; under nitrogen conditions, calcine the dried solid at 960°C for 2.5h, cool naturally to room temperature, and grind it in a ball mill at a speed of 400r / min for 4h to obtain nitrogen-doped titanium carbide, that is, modified titanium carbide;

[0069] S43, at room temperature, 28 parts by mass of modified titanium carbide, 15 parts of tungsten carbide, 2 parts of polyethylene glycol 200 and 75 parts of anhydrous ethanol were subjected to ultrasonic treatment at a power of 550 W for 2.5 hours, the temperature was raised to 90° C., after being completely dried, the mixture was ground with 4 parts of molybdenum disulfide in a ball mill at a speed of 400 r / min for 4 hours, and passed through a 200-mesh sieve to prepare a modified filler;

[0070] S44, adding 4 parts of hydroxy silicone oil and 1.5 parts of KH550 to 95 parts of epoxy resin, and preparing a modified epoxy resin after ultrasonic dispersion at 83° C.;

[0071] S45, 55 parts of modified epoxy resin, 4 parts of sodium carboxymethyl cellulose, and 0.8 parts of BYK-024 were stirred at a speed of 650 r / min for 1.3 h, and then 18 parts of modified filler, 6 parts of talc and 4 parts of diaminodiphenylmethane were added, the speed was increased to 900 r / min and the stirring was continued for 1.5 h. After being completely mixed, the coating was filtered through a 200-mesh sieve to obtain a coating;

[0072] S46. Sandblast the surface of the cylinder seat substrate. 25-mesh white corundum is used for sandblasting. The pressure of compressed air during sandblasting is 0.5 MPa, the sandblasting distance is 130 mm, and the sandblasting angle is 80°.

[0073] S47. Spray the coating on the surface of the cylinder seat substrate treated in step S46 by ultrasonic spraying. After coating, let the sample stand until it is completely cured and dried to obtain a cylinder seat with a coating on the surface. The ultrasonic power is 55 W, the ultrasonic frequency is 160 kHz, and the spraying distance is 50 mm.

[0074] Example 3

[0075] S11. Smelting:

[0076] Under nitrogen conditions, 90 parts of aluminum, 13 parts of manganese, 5 parts of zinc, 8 parts of chromium, 3 parts of antimony, 15 parts of silicon, 8 parts of titanium, 5 parts of molybdenum, 5 parts of nickel, 5 parts of vanadium, and 5 parts of magnesium were mixed evenly by weight, added into a 600°C boiler and kept for 1 hour, heated to 700°C and kept for 3 hours, and then the temperature was raised to 850°C for refining for 5 hours, and a degassing operation was performed after refining, and degassing was performed at a temperature of 700°C for 5 hours to prepare a refined liquid;

[0077] S12, molding:

[0078] At 750℃, the refined liquid is centrifugally cast at a speed of 1300r / min, and the refined liquid is poured into the mold. The temperature of the mold is 500℃, and the mold casting is performed with a flow rate of 20m 3 / h of cooling water, and after solidification, the temperature is maintained at 320°C for 23 hours, and finally air-cooled to room temperature to obtain a formed cylinder seat;

[0079] S13, heat treatment:

[0080] The molded cylinder seat is heated to 380°C at a speed of 6°C / s, kept at this temperature for 1.5 hours, then cooled to room temperature by air cooling at a speed of 7°C / s, then heated to 450°C at a speed of 10°C / s, kept at this temperature for 2 hours, and then slowly cooled to room temperature by cooling water at a cooling speed of 3°C / s;

[0081] S14, Surface treatment:

[0082] After the heat-treated cylinder seat is trimmed, washed with water, and dried, a coating treatment is performed on the surface, and the coating thickness is 20 μm to obtain the cylinder seat with a stable metallographic structure.

[0083] The coating preparation process is as follows:

[0084] S41, at room temperature, titanium carbide, graphene oxide and ethanol in a mass ratio of 30:10:70 were mixed by ultrasound, the pH of the suspension was adjusted to 7 with acetic acid, the mixture was stirred for 4 hours, the temperature was increased to 115° C., the mixture was dried and crushed to prepare pretreated titanium carbide;

[0085] S42. At 60°C, glycine and pretreated titanium carbide in a mass ratio of 1:1 were added to deionized water, and a uniformly dispersed mixed solution was obtained after ultrasonic treatment for 1 hour. The mixture was further heated to 110°C, and the water was evaporated under stirring. The obtained solid was collected and dried in a vacuum drying oven. Under nitrogen conditions, the dried solid was calcined at 1000°C for 3 hours, cooled naturally to room temperature, and then ground in a ball mill at a speed of 400 r / min for 5 hours to obtain nitrogen-doped titanium carbide, that is, modified titanium carbide.

[0086] S43, at room temperature, 30 parts by mass of modified titanium carbide, 20 parts by mass of tungsten carbide, 3 parts by mass of polyethylene glycol 200 and 80 parts by mass of anhydrous ethanol were subjected to ultrasonic treatment at a power of 600 W for 3 hours, the temperature was raised to 100° C., after being completely dried, the mixture was ground with 5 parts of molybdenum disulfide in a ball mill at a speed of 400 r / min for 5 hours, and passed through a 200-mesh sieve to prepare a modified filler;

[0087] S44, adding 5 parts of polydimethylsiloxane and 2 parts of KH550 to 100 parts of epoxy resin, and preparing a modified epoxy resin after ultrasonic dispersion at 85° C.;

[0088] S45, 60 parts of modified epoxy resin, 5 parts of sodium carboxymethyl cellulose, and 1 part of BYK-065 were stirred at a speed of 700 r / min for 1.5 hours, and then 20 parts of modified filler, 8 parts of talc and 5 parts of isophorone diamine were added, the speed was increased to 1000 r / min and stirring was continued for 2 hours, and after being completely mixed, the coating was filtered through a 200 mesh sieve;

[0089] S46. Sandblast the surface of the cylinder seat substrate. 30-mesh white corundum is used for sandblasting. The pressure of compressed air during sandblasting is 0.6 MPa, the sandblasting distance is 150 mm, and the sandblasting angle is 90°.

[0090] S47. Spray the coating on the surface of the cylinder seat substrate treated in step S46 by ultrasonic spraying. After coating, let the sample stand until it is completely cured and dried to obtain a cylinder seat with a coating on the surface. The ultrasonic power is 60 W, the ultrasonic frequency is 180 kHz, and the spraying distance is 60 mm.

[0091] Comparative Example 1

[0092] The difference between Comparative Example 1 and Example 1 is that the modified titanium carbide in Comparative Example 1 is not treated with graphene oxide when it is prepared, and the other operations are the same.

[0093] Comparative Example 2

[0094] The difference between Comparative Example 2 and Example 1 is that the modified titanium carbide in Comparative Example 2 is not treated with glycine, and the other operations are the same.

[0095] Comparative Example 3

[0096] The difference between Comparative Example 3 and Example 1 is that molybdenum disulfide is not added when preparing the modified filler in Comparative Example 3, and the other operations are the same.

[0097] Comparative Example 4

[0098] The difference between Comparative Example 4 and Example 1 is that the preparation process of the filler in Comparative Example 4 is as follows: at room temperature, 25 parts by mass of titanium carbide, 10 parts of tungsten carbide, 1 part of polyethylene glycol 200 and 70 parts of anhydrous ethanol are subjected to ultrasonic treatment with a power of 500 W for 2 hours, the temperature is increased to 85°C, and after complete drying, they are ground in a ball mill at a speed of 400 r / min for 3 hours, and passed through a 200-mesh sieve to prepare a filler; the rest of the operations are the same.

[0099] Comparative Example 5

[0100] The difference between Comparative Example 5 and Example 1 is that the epoxy resin in Comparative Example 5 is not modified, and the other operations are the same.

[0101] Performance testing:

[0102] 1. The wear resistance of the present invention is measured by using a JM IV abrasion tester and a rotating friction rubber wheel method, and the average value of the coating mass loss (weight loss method) after grinding at 1000 grinding revolutions is used. The load is 10N, the rotation speed is 500r / min, the test temperature is 25°C, the relative humidity is 50%, and the mass is tested to an accuracy of 0.01mg. The average value of 3 measurements is taken as the result;

[0103] 2. According to ASTM E18-2018 standard test method for Rockwell hardness of metal materials, the Rockwell hardness is tested. The test results are shown in Table 1 below:

[0104] Table 1

[0105]

[0106] According to the above data, it can be seen that the cylinder seat prepared by the present invention has good hardness and good wear resistance.

[0107] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A casting process for producing a cylinder block with a stable metallographic structure, characterized in that: The following steps are involved: S11. Smelting: Under nitrogen conditions, 80-90 parts of aluminum, 9-13 parts of manganese, 3-5 parts of zinc, 5-8 parts of chromium, 1-3 parts of antimony, 10-15 parts of silicon, 5-8 parts of titanium, 2-5 parts of molybdenum, 3-5 parts of nickel, 3-5 parts of vanadium, and 3-5 parts of magnesium are stirred evenly by weight, added into a 570-600°C boiler and kept for 0.5-1h, heated to 670-700°C and kept for 2-3h, then the temperature is raised to 800-850°C for refining for 3-5h, and degassed after refining, and degassed at a temperature of 650-700°C for 4-5h to prepare a refined liquid; S12, molding: The refined liquid is centrifugally casted at a speed of 1100 to 1300 r / min at 700 to 750° C., poured into a mold, molded, cooled by cooling water, and after solidification, the temperature is maintained at 300 to 320° C. for 20 to 23 hours, and finally air-cooled to room temperature to obtain a formed cylinder seat; S13, heat treatment: The formed cylinder seat is heated to 350-380°C at a speed of 4-6°C / s, kept warm for 0.5-1.5h, then cooled to room temperature by air cooling at a speed of 5-7°C / s, then heated to 400-450°C at a speed of 7-10°C / s, kept warm for 1-2h, and then slowly cooled to room temperature by cooling water at a cooling speed of 2-3°C / s; S14, Surface treatment: The heat-treated cylinder seat is trimmed, washed with water, and dried, and then coated on the surface with a coating thickness of 10 to 20 μm to obtain the cylinder seat with a stable metallographic structure.

2. The casting process for producing a cylinder block with a stable metallographic structure according to claim 1 is characterized in that: In step S12, the temperature of the mold is 450-500°C.

3. The casting process for producing a cylinder block with a stable metallographic structure according to claim 1, characterized in that: In step S12, the flow rate of the cooling water is 10-20 m 3 / h.

4. The casting process for producing a cylinder block with a stable metallographic structure according to claim 1, characterized in that: In step S14, the coating is prepared as follows: S41. At room temperature, titanium carbide, graphene oxide and ethanol in a mass ratio of (25-30): (5-10): (50-70) are mixed by ultrasound, the pH of the suspension is adjusted to 6-7 with acetic acid, the mixture is stirred for 2-4 hours, the temperature is increased to 105-115° C., the mixture is dried and crushed to prepare pretreated titanium carbide; S42. At 50-60°C, add glycine and pretreated titanium carbide in a mass ratio of 1:1 to deionized water, perform ultrasonic treatment for 0.5-1h to obtain a uniformly dispersed mixed solution, continue to heat to 100-110°C, evaporate the water under stirring, collect the obtained solid and dry it in a vacuum drying oven; under nitrogen conditions, calcine the dried solid at 920-1000°C for 2-3h, cool naturally to room temperature, and grind it in a ball mill at a speed of 400r / min for 3-5h to obtain nitrogen-doped titanium carbide, that is, modified titanium carbide; S43. At room temperature, 25 to 30 parts by mass of modified titanium carbide, 10 to 20 parts of tungsten carbide, 1 to 3 parts of polyethylene glycol 200 and 70 to 80 parts of anhydrous ethanol are subjected to ultrasonic treatment at a power of 500 to 600 W for 2 to 3 hours, the temperature is raised to 85 to 100° C., and after complete drying, the mixture is ground with 2 to 5 parts of molybdenum disulfide in a ball mill at a speed of 400 r / min for 3 to 5 hours, and passed through a 200-mesh sieve to prepare a modified filler; S44, adding 2 to 5 parts of an organosilicon modifier and 1 to 2 parts of a silane coupling agent to 90 to 100 parts of an epoxy resin, and preparing a modified epoxy resin after ultrasonic dispersion at 80 to 85° C.; S45, stirring 50-60 parts of modified epoxy resin, 3-5 parts of dispersant, and 0.5-1 part of defoamer at a speed of 600-700 r / min for 1-1.5 hours, then adding 15-20 parts of modified filler, 5-8 parts of talcum powder and 3-5 parts of curing agent, increasing the speed to 850-1000 r / min and continuing stirring for 1-2 hours, mixing completely and filtering through a 200 mesh sieve to obtain a coating; S46. Sandblast the surface of the cylinder seat substrate. Use 20-30 mesh white corundum for sandblasting. The pressure of compressed air during sandblasting is 0.4-0.6 MPa, the sandblasting distance is 100-150 mm, and the sandblasting angle is 70-90°. S47, spraying the coating on the surface of the cylinder seat substrate treated in step S46 by ultrasonic spraying, and leaving the sample to stand until it is completely cured and dried to obtain a cylinder seat with a coating on the surface.

5. The casting process for producing a cylinder block with a stable metallographic structure according to claim 4 is characterized in that: In step S44, the organosilicon modifier is one of hydroxy silicone oil and polydimethylsiloxane.

6. The casting process for producing a cylinder block with a stable metallographic structure according to claim 4, characterized in that: In step S44, the silane coupling agent is one of KH550, KH560 or KH570.

7. The casting process for producing a cylinder block with a stable metallographic structure according to claim 4, characterized in that: In step S45, the curing agent is one of diaminodiphenylmethane and isophoronediamine.

8. The casting process for producing a cylinder block with a stable metallographic structure according to claim 4, characterized in that: In step S45, the dispersant is one of sodium carboxymethyl cellulose, sodium carboxyethyl cellulose and polyethylene glycol 200.

9. The casting process for producing a cylinder block with a stable metallographic structure according to claim 4, characterized in that: In step S45, the defoaming agent is one of BYK-065, BYK-024 and Tego-901.

10. The casting process for producing a cylinder block with a stable metallographic structure according to claim 4, characterized in that: In step S47, the parameters of the ultrasonic spraying are: ultrasonic power of 50-60 W, ultrasonic frequency of 120-180 kHz, and spraying distance of 30-60 mm.